Chemoimmunotherapy resistant follicular lymphoma: predictors of resistance, association with transformation and prognosis. Issue 11 (November 2014) - Mozessohn, Lee; Cheung, Matthew C.; Crump, Michael; Buckstein, Rena; Berinstein, Neil; Imrie, Kevin; Kuruvilla, John; Piliotis, Eugenia; Kukreti, Vishal
Abstract: Follicular lymphoma (FL) is characterized by an initial response to treatment with inevitable relapse. We evaluated chemoimmunotherapy resistance (CIR resistance) including transformation. We identified patients who received rituximab combination therapy for symptomatic FL. CIR resistance was defined as disease progression during rituximab-based chemoimmunotherapy, rituximab maintenance or within 6 months of treatment completion. Our primary outcome was time to early progression (CIR resistance). Between July 2006 and April 2010, 132 patients met the inclusion criteria and 22 (16.7%) demonstrated CIR resistance with a median follow-up of 33 months. High-risk Follicular Lymphoma International Prognostic Index (FLIPI) score was predictive of CIR resistance (hazard ratio [HR] 2.43; 95% confidence interval [CI], 1.4–4.1; p = 0.001). Overall, eight patients (36.3%) transformed (biopsy-proven), with no transformation in the chemoimmunotherapy responder group. Median overall survival in the CIR resistant group was 47 months. Patients with CIR resistance had high rates of histologic transformation and shorter survival with poor response to next therapy.